2022
DOI: 10.1111/hir.12444
|View full text |Cite
|
Sign up to set email alerts
|

NHS librarians collaborate to develop a search bank peer reviewing and sharing COVID‐19 searches: an evaluation

Abstract: Background Responding to the COVID‐19 pandemic, Health Education England (HEE) mobilised a group of expert searchers from NHS libraries in England to develop a platform for librarians to share peer reviewed search strategies and results on the Knowledge for Healthcare website. Objectives (1) To document the origins of the COVID‐19 search bank, (2) evaluate attitudes of NHS librarians in England towards the search bank and (3) identify lessons learned and consider whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…When it comes to searching there is much we can learn from one another, as demonstrated by Gorring et al (2022) in their evaluation of the collaborative development of a search bank for sharing and peer reviewing search strategies. Combining structured interviews with a questionnaire survey ( n = 85) of the UK NHS library community, Gorring et al found that respondents valued collaboration, believing that the quality of searches benefited from the paired buddy system to peer review submitted search strategies.…”
mentioning
confidence: 99%
“…When it comes to searching there is much we can learn from one another, as demonstrated by Gorring et al (2022) in their evaluation of the collaborative development of a search bank for sharing and peer reviewing search strategies. Combining structured interviews with a questionnaire survey ( n = 85) of the UK NHS library community, Gorring et al found that respondents valued collaboration, believing that the quality of searches benefited from the paired buddy system to peer review submitted search strategies.…”
mentioning
confidence: 99%